2018
DOI: 10.35196/rfm.2018.3.227-236
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSIDAD GENÉTICA DE CHILE HABANERO (Capsicum chinense Jacq.) MEDIANTE ISSR

Abstract: El chile habanero (Capsicum chinense Jacq.) es distintivo de la Península de Yucatán, México; sin embargo, los estudios de diversidad genética a nivel molecular en este cultivo son escasos. El presente trabajo se planteó con el objetivo de caracterizar la diversidad genética del germoplasma de chile habanero, mediante marcadores ISSR. El material genético consistió en 60 poblaciones criollas de chile habanero recolectadas en los estados de Yucatán, Campeche, Quintana Roo y Tabasco, México, las cuales fueron ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
1
10
0
4
Order By: Relevance
“…However, despite having fewer accessions (two accessions: Bolita and Pico Paloma), group two had a genetic diversity value similar to that of group one, indicating that the accessions that formed this group present high levels of genetic diversity, and that the genetic diversity found for all accessions evaluated was high. This result is similar to that found by Lopéz-Espinoza et al [9] for 60 landraces of Capsicum chinense from southern Mexico using three ISSR primers and were higher than those by Hanáček et al [46] who reported an average polymorphism of 0.33 among 41 accessions of C. annuum.…”
Section: Genetic Diversity Of Nine Accessions Of Capsicum Species Frosupporting
confidence: 90%
See 2 more Smart Citations
“…However, despite having fewer accessions (two accessions: Bolita and Pico Paloma), group two had a genetic diversity value similar to that of group one, indicating that the accessions that formed this group present high levels of genetic diversity, and that the genetic diversity found for all accessions evaluated was high. This result is similar to that found by Lopéz-Espinoza et al [9] for 60 landraces of Capsicum chinense from southern Mexico using three ISSR primers and were higher than those by Hanáček et al [46] who reported an average polymorphism of 0.33 among 41 accessions of C. annuum.…”
Section: Genetic Diversity Of Nine Accessions Of Capsicum Species Frosupporting
confidence: 90%
“…In Mexico, Aguilar-Meléndez [6] considered the Yucatan Peninsula (Yucatán, Campeche and Quintana Roo states) as an important region of domestication and diversification of Capsicum annuum. Despite this importance, very few studies have focused on the genetic diversity of Capsicum throughout the entire Peninsula; instead, the central area of the Yucatan Peninsula, that is, Yucatan state [7][8][9], has received all the attention. Thus, the total diversity present in the entire Yucatan Peninsula, inclusive of the other two states (Campeche and Quintana Roo states), is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these techniques is plant genetic improvement, a method that has been widely used since pre-Hispanic times to improve food production for humanity [17]. In Capsicum, as in other horticultural species, obtaining crop varieties has generally been carried out through the evaluation and selection of promising genotypes within the populations and the existing genetic diversity, or by following the schemes of classical genetic improvement and hybridization [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, is important to use the existing genetic diversity to produce improved varieties of habanero pepper that can adapt to new local and regional agroclimatic con- through the evaluation and selection of promising genotypes within the populations and the existing genetic diversity, or by following the schemes of classical genetic improvement and hybridization [17,18]. In this regard, is important to use the existing genetic diversity to produce improved varieties of habanero pepper that can adapt to new local and regional agroclimatic conditions to enhance high productivity.…”
Section: Introductionmentioning
confidence: 99%